PHILIPPINE AND INTERPOL COOPERATION IN ADDRESSING CYBERSEX CRIME IN THE PHILIPPINES - Usman , Inda Rowahita; Haryanto, Agus (Journal of Social Political Sciences, 2024)
The Philippines is the top four countries in prostitution crime at the world level and number two in Asia. One of the growing crimes of prostitution in the Philippines is the use of cybercrime in the form of cybersex. This paper seeks to explore how the Philippine government is working to address this issue. For that reason, this study uses qualitative research methods with transnational crime thought frameworks, cybercrime, and international cooperation. In this paper, the findings reveal that to address cybersex crime, the Philippine government found this issue to be included in cross-border crime. Therefore, the Philippine government cooperates with INTERPOL. Then, the cooperation between the two results in a joint operation called Operation Strikeback.